Spanish Cultural Standards in the Work and Study Environment from the Czech Perspective - Ošťádalová, Michaela (2020)
This diploma thesis identifies several Spanish cultural standards in work and study environment based on the Czech perspective. At first, three fundamental questions are posed: How is work, overtime, and free time perceived in Spanish culture? What is their view on authorities? Are there any differences between the two inspected environments? To answer them, the author had conducted 24 interviews with the Czech women who had worked or studied in Spain, thus identifying 12 cultural standards in total. The thesis itself consists of five major chapters. The first one provides the reader with necessary background information about what exactly culture or cultural standard is, while also explicating work made by several prominent authors in the field such as G. Hofstede or E. Meyer, for example. The following chapter introduces facts about Spain and studying there. Next, the research is explained and its results presented. Subsequently, the research results are compared to those of the two aforementioned authors. Finally, there are recommendations made especially for those that would like to work or study in Spain.